1989
DOI: 10.1021/j100338a095
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrochemistry of alkyl ring-substituted polyanilines

Abstract: Poly(o-toluidine), poly(m-toluidine), and poly(o-ethylaniline) have been synthesized chemically and electrochemically. The polymers were characterized by elemental analysis, UV-vis spectroscopy, and cyclic voltammetry. Elemental analysis data suggest that the protonated polymers are derived from bases containing ca. 37-54% oxidized (imine) units. Upon treatment with 1 M HC1, conductivities of the polymers increase dramatically from ca. 10~8 S/cm to ca. 1CT1 S/cm for polytoluidines and to ca. 1CT3 S/cm for poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
182
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(203 citation statements)
references
References 0 publications
15
182
0
2
Order By: Relevance
“…However, the main disadvantages of polyaniline are its insolubility in common organic solvents and its infusibility 19 . Previous studies revealed that introducing mono alkyl or alkoxy substituents on the ortho position of the phenyl ring resulted in an increase of solubility, and at the same time, a decrease in conductivity [20][21][22][23][24][25] . However, the presence of 2,5-dialkoxy substituted on the phenyl rings resulted in an enhanced conductivity 12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the main disadvantages of polyaniline are its insolubility in common organic solvents and its infusibility 19 . Previous studies revealed that introducing mono alkyl or alkoxy substituents on the ortho position of the phenyl ring resulted in an increase of solubility, and at the same time, a decrease in conductivity [20][21][22][23][24][25] . However, the presence of 2,5-dialkoxy substituted on the phenyl rings resulted in an enhanced conductivity 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Apesar dessa diferença nos meros, a POMA apresenta propriedades físicas bastante semelhantes às da PANi. Porém, sua solubilidade é maior que a da PANi, o que se deve a dois efeitos 11 promovidos pela presença do grupo metoxi: torção induzida na cadeia polimérica e aumento da polaridade da mesma 12,13 . Assim como a PANi, a POMA pode ser obtida em diferentes estados de oxidação: leucoesmeraldina, esmeraldina e pernigranilina, sendo que o estado de oxidação esmeraldina pode ser encontrado nas formas de base (não condutor elétrico) ou de sal (condutor elétrico).…”
Section: Introductionunclassified
“…Ir= r.,4i -exp(-N 4ki-k e-kiT-t)] T. --r << r.. (22) Note that the integral in eq. (14) runs from r = 0 to r and that eq.…”
Section: Theory and Resultsmentioning
confidence: 99%